Spatial Analysis Of Transportation And Communication Sector Competitiveness In Jember District - Sebastiana Viphindrartin; Endah Kurnia Lestari; Imro'atul Husna Afriani (MediaTrend, 2021)
This study investigates the comparative advantage between sub-districts in the district of Jember using the shift-share analysis method with data periods from 2009 to 2013. From the results of the shift-share analysis, it can be seen that there are several sub-districts in Jember Regency that have competitive advantages in the transportation and communication sector and sub-districts that do not have a competitive advantage in the transportation and communication sector.